Life cycle based evaluation of harvested rainwater use in toilets and for irrigation. (15th May 2015) - Devkota, Jay; Schlachter, Hannah; Apul, Defne
Abstract: Harvested rainwater is an alternative water source for buildings, especially for non-potable uses such as irrigation and toilet flushing. While rainwater harvesting is perceived as a sustainable design approach, there is limited information on the environmental and economic performance of this technology. To address this literature gap, life cycle assessment and life cycle costing tools were applied for a dormitory that could potentially use harvested rainwater to flush toilets or to irrigate the lawn. Five scenarios were modeled including a new versus renovated building and irrigation versus toilet flushing water end use. The rainwater cisterns for all the scenarios were sized using the Yield After Spillage approach and long term daily precipitation of Toledo. Energy and greenhouse gas emissions were calculated using Economic Input Output Life Cycle Assessment (for construction phase and energy use by pump) and GaBi (for water and wastewater treatment) databases. The life cycle environmental impacts and costs were estimated and compared to the business as usual scenario, where the water supply demands are met by municipally supplied potable water in a combined or separate sanitary sewer network. It was discovered that energy and greenhouse gas emission payback periods can be achieved for almost every scenario. Yet cost payback periods of implementing harvested rainwater were found to be longer than the life time of the building except for two scenarios: using rainwater for irrigation in a renovation project and using rainwater for toilet flushing in a new construction project. These two scenarios had the lowest cost, energy and greenhouse gas emission impacts among all scenarios modeled. Reducing occupancy to match toilet flushing demand increased the per person impact. However, in general, the per person impacts were much lower than a person's impact from driving or electricity use. While separate sewers divert the stormwater runoff to the water bodies and thereby prevent the environmental problems resulting from combined sewer overflows, a rainwater harvesting system connected to separate sewers was found to reduce the energy and greenhouse gas emissions less than so if the rainwater harvesting system were connected to combined sewers. Highlights: Construction and operation phases of rainwater harvesting (RWH) systems were studied. Cost, energy, and greenhouse gas emissions (GHG) from RWH systems were quantified. RWH systems were more preferable in combined than in separate sewers. In new construction rainwater in toilets was lower impact than its use in irrigation. Impacts from toilets and irrigation are much smaller than electricity use & driving.